2018
DOI: 10.1016/j.bbr.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Repeated social stress leads to contrasting patterns of structural plasticity in the amygdala and hippocampus

Abstract: Previous studies have demonstrated that repeated immobilization and restraint stress cause contrasting patterns of dendritic reorganization as well as alterations in spine density in amygdalar and hippocampal neurons. Whether social and ethologically relevant stressors can induce similar patterns of morphological plasticity remains largely unexplored. Hence, we assessed the effects of repeated social defeat stress on neuronal morphology in basolateral amygdala (BLA), hippocampal CA1 and infralimbic medial pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 48 publications
7
33
0
Order By: Relevance
“…Repeated social stress in rats induces enhanced dendritic arborization in the basal dendrites of BLA pyramidal neurons. This effect is accompanied by an increase in social avoidance behavior suggesting stress-induced increase in social anxiety in the rats [66]. This confirms the previously published effect using models of physical stressors such as restraint and immobilization [50,69].…”
Section: Amygdalasupporting
confidence: 90%
See 3 more Smart Citations
“…Repeated social stress in rats induces enhanced dendritic arborization in the basal dendrites of BLA pyramidal neurons. This effect is accompanied by an increase in social avoidance behavior suggesting stress-induced increase in social anxiety in the rats [66]. This confirms the previously published effect using models of physical stressors such as restraint and immobilization [50,69].…”
Section: Amygdalasupporting
confidence: 90%
“…Chronic social defeat stress in susceptible mice decreases dendritic spine density in the neurons of CA3 and dentate gyrus region of hippocampus [72]. Repeatedly defeated rats from a feral strain (wild-type Groningen rats) exhibited robust decrease in spine density in the CA1 pyramidal apical dendrites [66]. Another study showed a significant decrease in stubby spines, and an increase in long-thin spines within the CA1 stratum radiatum region when adolescent male mice were subjected to 10 days of defeat [73].…”
Section: Hippocampusmentioning
confidence: 97%
See 2 more Smart Citations
“…Due to their roles in processing of emotion, emotional memory and stress response [104][105][106][107], the mesial temporal amygdala, hippocampus, and entorhinal cortex (BA28, within the adjacent parahippocampal gyrus) are also thought to be involved in STBs. However, findings reported have been inconsistent.…”
Section: Amygdala and Hippocampusmentioning
confidence: 99%